SOCIAL MEDIA MARKETING ANALYSIS OF COMMNIGHTRUN EVENT - Muhammad Dhavin Ardiansyah; Nur Maghfirah Aesthetika (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to analyze the implementation of social media marketing strategies in enhancing visibility and audience participation for CommNightRun, the first night run event organized by Communication Science students at Universitas Muhammadiyah Sidoarjo. Method: Employing a qualitative approach with a case study design, data were obtained through in-depth interviews with event organizers, observations of official social media accounts (Instagram, TikTok, and the event website), and documentation of promotional materials. Results: The findings reveal that the social media marketing strategy was systematically structured based on Singh’s five dimensions of social media marketing: online community, interaction, content sharing, accessibility, and credibility. The use of interactive content, strategic scheduling, and visually engaging, emotionally resonant messages effectively increased audience engagement and participation. Novelty: This study contributes to the understanding of how student-led events can leverage social media marketing to build visibility and audience loyalty, offering a practical framework for future campus-based digital marketing initiatives.